Seroprevalence, risk factors of leptospirosis seropositivity and effectiveness of leptospirosis health intervention module in improving knowledge, attitude, belief and practice on leptospirosis among wet market workers in Kelantan - Rahman, Mas Harithulfadhli Agus Ab (2018)
Leptospirosis is a zoonotic disease which affect human and animal globally. The disease is known to be related to occupations which are exposed to contaminated environment. This study aims to determine the seroprevalence, factors associated with leptospirosis and effectiveness of Leptospirosis Health Intervention Module among wet market workers in Kelantan. In Phase One, a cross sectional study was conducted among 232 wet market workers who fulfilled the study criteria and were randomly selected from two main wet markets in Kelantan. Information regarding sociodemographic, work-related characteristics and recreational activities were collected using validated KABP questionnaire on leptospirosis. Blood samples were collected and analysed using microscopic agglutination test (MAT). In Phase Two, an intervention study was conducted. Respondents from phase one were divided into control and intervention groups based on their workplace. Intervention group received the intervention program based on Leptospirosis Health Intervention Module and control group received no intervention. Knowledge, attitude, belief and practice of respondents were assessed using validated KABP questionnaire before and after six weeks of the intervention. The mean age of respondents was 42.6 (14.68) years old and majority of them were female (63.4%). The overall seroprevalence of leptospirosis among wet market workers was 33.6% and the predominant serovars was Autumnalis with 18.2%. The factors associated with leptospirosis seropositivity was age (AOR 1.02; 95% CI: 1.004, 1.043) and not using glove during work (AOR 2.45; 95% CI: 1.02, 5.87). There were significant increase of knowledge, attitude, belief and practice scores among intervention group compared to control group. For knowledge section, intervention group showed significantly higher score (p<0.001) compare to control group with the adjusted mean difference between groups was 12.93 (95% CI: 8.47, 17.39). For attitude section, intervention group showed significantly higher score (p=0.001) compare to control group with the adjusted mean difference between groups was 5.55 (95% CI: 2.28, 8.81). For belief section, intervention group showed significantly higher score (p<0.001) compare to control group with the adjusted mean difference between groups was 7.21 (95% CI: 3.43, 10.99). For practice section, intervention group showed significantly higher score (p<0.001) compare to control group with the adjusted mean difference between groups was 7.35 (95% CI: 3.64, 11.05). The findings in this study showed that the seroprevalence of leptospirosis among wet market workers in Kelantan was high and associated with age and not using protective clothing at work. The Leptospirosis Health Intervention Module was effective in improving the knowledge, attitude, belief and practice regarding leptospirosis among the workers. Thus, it is important to increase awareness regarding this disease among the workers and Leptospirosis Health Intervention Module can be used as a tool for health education for this risk group.